PERENCANAAN PROGRAM LITERASI DIGITAL DALAM MENINGKATKAN KOMPETENSI PEMBELAJARAN ABAD 21 DI SEKOLAH DASAR KABUPATEN ACEH BARAT - Liesmaniar, Cut; Mulyadi, Said; Iskandar, Iskandar (Puteri Hijau : Jurnal Pendidikan Sejarah, 2024)
The aim of this research is to determine the planning of a digital literacy program in improving 21st century learning competencies in West Aceh Regency Elementary Schools implemented at Kuala Bhee State Elementary School (SDN), Pasi Aceh SDN, Padang Jawa SDN, Lung Tanoh Tho SDN, Blang Mee SDN , Paya Dua Elementary School, and Cot Lagan Elementary School, West Aceh Regency. The research method used is a qualitative method with data collection instruments using interview techniques and literature study. Interviews were conducted with school principals, school supervisors and class teachers. The time of the research was in September 2023. The results of the research can be concluded that the planning of the digital literacy program was carried out through school meetings, planning of teachers/educational personnel who handle the digital literacy program, planning of teaching materials/literacy topics taught, planning of facilities and infrastructure used in the program digital literacy, planning the budget used, planning the implementation of the digital literacy program and monitoring planning carried out to control the implementation of the digital literacy program can run as expected. The implementation of the digital literacy program in improving 21st century learning in West Aceh Regency Elementary Schools is carried out through the Computer-Based National Assessment (ANBK) program, through a 15 minute reading program before morning lessons, reading corners, literacy creations for each end-of-semester activity, wall magazine program ( mading) and a short verse literacy program every Friday morning. Barriers to implementing digital literacy programs include that there are still teachers who do not understand digital literacy, there are teachers who do not carry out digital literacy program tasks, limited digital skills and digital facilities as a learning medium for students, internet networks and electricity networks often experiencing disruptions and limited digital library infrastructure. at school.